Is risk of Kaposi's sarcoma in AIDS patients in Britain increased if sexual partners came from United States or Africa?. Issue 6777 (16th March 1991) - Beral, V; Bull, D; Jaffe, H; Evans, B; Gill, N; Tillett, H; Swerdlow, A J
Abstract : OBJECTIVE–To determine whether the risk of Kaposi's sarcoma in patients with AIDS is increased by sexual contact with groups from abroad with a high incidence of Kaposi's sarcoma. DESIGN–Analysis of risk of Kaposi's sarcoma in patients with AIDS, according to country of origin of their sexual partners. SETTING–United Kingdom. PATIENTS–2830 patients with AIDS reported to the Communicable Disease Surveillance Centre and the Communicable Disease (Scotland) Unit up to March 1990, of whom 566 had Kaposi's sarcoma. MAIN OUTCOME MEASURES–Percentage of patients with AIDS who had Kaposi's sarcoma. RESULTS–537 of 2291 homosexual or bisexual men (23%) with AIDS had Kaposi's sarcoma; 10% (14/135) of the men and women who acquired HIV by heterosexual contact had Kaposi's sarcoma. None of the 316 subjects who acquired HIV through non-sexual routes had Kaposi's sarcoma. Kaposi's sarcoma was more common among homosexual men whose likely source of infection included the United States (171/551, 31%) or Africa (9/34, 26%) than among those infected in the United Kingdom (119/625, 19%) (p less than 0.05). CONCLUSION–The data suggest that Kaposi's sarcoma is caused by a sexually transmissible agent which was introduced into the British homosexual population mainly from the United States [corrected].